Pengaruh Realisasi PMA, PMDN dan Tingkat Partisipasi Angkatan Kerja terhadap Pertumbuan Ekonomi di Provinsi Bali - Sophie Aulia; M. Afdal Samsuddin (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the influence of Foreign Direct Investment (FDI), Domestic Investment (DI), and Labor Force Participation Rate (LFPR) on the growth of Gross Regional Domestic Product (GRDP) in Bali Province. This research employs a quantitative approach using secondary time series data on an quartal basis from 2015 to 2022, obtained from the Central Statistics Agency (BPS) and other relevant institutions. The analytical method used is multiple linear regression with the assistance of EViews 9 software. The results show that, partially, FDI, DI, and LFPR have a positive and significant effect on GRDP growth in Bali Province. Simultaneously, the three variables also have a significant influence on GRDP. The Adjusted R-Squared value of 0.543 indicates that approximately 54.3% of the variation in GRDP can be explained by FDI, DI, and LFPR, while the remaining variation is influenced by other variables outside the model. However, the regression model experiences autocorrelation, indicating that there are time dynamics not fully captured by the model. This study highlights the importance of investment and the optimization of the labor force in supporting regional economic growth.